PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PECAHAN DI KELAS V SDN 2 BANDA ACEH - Linda Vitoria; Vivi Vanda Akhwilla (Universitas Syiah Kuala, 2018)
Numbered Heads Together (NHT) is a teaching approach that promotes students' involvement in group discussion. This article reports a classroom action research conducted to improve students’ learning acievement in fractions at Grade V SDN 2 Banda Aceh. The participants were students of Class VA which consisted of 34 students, 22 boys and 12 girls. The research was conducted in 2 cycles, each consisted of 4 classroom meetings. The procedure of the research involved four stages: planning, action, observation, and reflection. The research questions covered students’ learning activities, students’ learning outcomes, and students’ responses on the implementation of NHT in the teaching of fractions. Results show that there were improvements in students’ learning activity from the average score of 2,57 in cycle 1 to 3,04 in cycle 2. Students’ learning outcomes improved from the average score of 66,30 in cycle 1 to 75,38 in cycle 2. Students’ responses in cycle 1 was 82,35% positive and increased to 88,24% in cycle 2. These results imply that the implementation of NHT is beneficial for students’ learning.